(untitled) (Eastern Librarian, 2012)
The task of purging some records and retaining others for long term preservation in an archival repository has not been an easy one for records professionals. This task is even made more difficult by the fact that what is destroyed as useless by todays standards can prove to be of invaluable use tomorrow. Ideally, archivists would want to keep everything to avoid such errors of judgment. However, the reality of limited storage facilities and the rate at which records are generated makes it impossible to preserve each and every record produced. This paper, co- authored by a graduate student and his mentor, discusses theories of records selection to help shape the difficult decisions of to keep and what to eliminate in an archival repository. DOI: http://dx.doi.org/10.3329/el.v23i1.12116 Eastern Librarian Vol.23(1) 2012 pp.24-36